Female Sex Hormones and Cardiac Pressure Overload Independently Contribute to the Cardiogenic Dementia Profile in Yucatan Miniature Swine - Hayward, Grant C.; LeBlanc, Paul J.; Emter, Craig A.; Nyarko, Jennifer N. K.; Mousseau, Darrell D.; MacPherson, Rebecca E. K.; Olver, T. Dylan (Frontiers in Cardiovascular Medicine, 2019)
Postmenopausal women with heart failure (HF) frequently exhibit cardiogenic dementia. Using a pre-clinical swine model of postmenopausal HF, we recently demonstrated that experimental menopause (ovariectomy; OVX) and HF (6-month cardiac pressure overload/aortic banding; AB) independently altered cerebral vasomotor control and together impaired cognitive function. The purpose of this study was to examine the prefrontal cortex and hippocampus tissues from these animals to assess whether OVX and HF are associated with neurologic alterations that may contribute to cardiogenic dementia. We hypothesized that OVX and HF would independently alter neuronal cell signaling in swine with postmenopausal cardiogenic dementia. Immunoblot analyses revealed OVX was associated with reduced estrogen receptor-α in both brain regions and HF tended to exacerbate OVX-induced deficits in the hippocampus. Further, OVX was associated with a reduction in the ratio of phosphorylated to total Akt and ERK in the hippocampus as well as decreased total Akt and synaptophysin in the prefrontal cortex. In contrast, HF was associated with a trend towards reduced phosphorylated: total ERK in the prefrontal cortex. In addition, HF was associated with decreased β-amyloid(1-38) in the prefrontal cortex and increased β-amyloid(1-38) in the hippocampus. Regional brain lipid analysis revealed OVX tended to increase total, saturated, and monounsaturated fatty acid content in the prefrontal cortex, with the greatest magnitude of change occurring in the AB-OVX group. The data from this study suggest that OVX and HF are independently associated with regional-specific neurologic changes in the brain that contribute to the cardiogenic dementia profile in this model. This pre-clinical swine model may be a useful tool for better understanding postmenopausal cardiogenic dementia pathology and developing novel therapies.